2020
DOI: 10.1126/sciadv.aba3458
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle antagonizes antiviral CD8 + T cell exhaustion

Abstract: CD8+ T cells become functionally impaired or “exhausted” in chronic infections, accompanied by unwanted body weight reduction and muscle mass loss. Whether muscle regulates T cell exhaustion remains incompletely understood. We report that mouse skeletal muscle increased interleukin (IL)–15 production during LCMV clone 13 chronic infection. Muscle-specific ablation of Il15 enhanced the CD8+ T cell exhaustion phenotype. Muscle-derived IL-15 was required to maintain a population of CD8+CD103+ muscle-infiltrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 37 publications
1
44
0
Order By: Relevance
“…Skeletal muscle secretes several cytokines and proteins named myokines, and it also functions as a primary site for glucose uptake and metabolism ( Cruz-Jentoft and Sayer, 2019 ; Johnson et al., 2013 ; Lee and Jun, 2019 ). In addition, skeletal muscle is reported to induce a microenvironment with less inflammation, sheltering a population of T cells from systemic inflammation and preventing their exhaustion ( Wu et al., 2020 ). Aging and various systemic diseases are associated with a decrease in the mass and function of skeletal muscle, which not only reduces the quality of life of patients but also leads to higher morbidity and mortality ( Cruz-Jentoft and Sayer, 2019 ; Johnson et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle secretes several cytokines and proteins named myokines, and it also functions as a primary site for glucose uptake and metabolism ( Cruz-Jentoft and Sayer, 2019 ; Johnson et al., 2013 ; Lee and Jun, 2019 ). In addition, skeletal muscle is reported to induce a microenvironment with less inflammation, sheltering a population of T cells from systemic inflammation and preventing their exhaustion ( Wu et al., 2020 ). Aging and various systemic diseases are associated with a decrease in the mass and function of skeletal muscle, which not only reduces the quality of life of patients but also leads to higher morbidity and mortality ( Cruz-Jentoft and Sayer, 2019 ; Johnson et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The TLR4 signaling pathway and other pattern recognition receptors (PRRS) in muscle cells can respond to inflammatory signals and influence metabolic changes [ 39 ]. The T cells and macrophages are involved in the production of inflammatory cytokines and insulin resistance in skeletal muscle [ 40 , 41 ]. Similarly, we found that Th17 cell differentiation, antigen processing and presentation, and chemokine signaling pathways were upregulated in the skeletal muscle of obese rabbits in the HFD-G group.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle has now been shown to have other functions, like harbouring and supplying anti-viral stem T-cells, hence, antagonising T-cell exhaustion and protecting proliferative potential during inflammation [ 127 ]. In contrast white adipose tissue plays a key role in adaptive immunity, and in excess, contributes to the altered immune function and chronic inflammation often associated with obesity [ 128 ].…”
Section: The Immune System Hormesis and Mitochondriamentioning
confidence: 99%